Beyond The Classroom: Empowering Social Care Character Through Islamic Education Via Student Executive Board - Mardhiah, Izzatul; Amaliyah, Amaliyah; Mintarja, Endang; Faidlaani, Akhmad; Izzudin, Ahmad (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2024)
Islamic Education (IE) in Higher Education is a compulsory course in Indonesia. However, it still dominantly assesses the cognitive aspect, while the learning competency of Islamic Education aims to form the religious character and social attitudes of students. Therefore, this study aims to develop indicators of student social care integrated with student organization activities. The indicator of social concern that has been validated and meets the content validity score will be used as a measuring tool for the attitude and skill components of students in Islamic Education learning. The process of developing indicators of social care integrated into student organization activities requires the ADDIE model development research method (Analysis, design, development, implementation, and evaluation, but in this study, there are only three stages: the first needs analysis, the second planning, and third development. The research subjects were students and lecturers of Islamic Education at Universitas Negeri Jakarta, Universitas Pendidikan Indonesia, and Universitas Muhammadiyah Jakarta. Data collection tools are questionnaires, interviews, and documentation studies. Data analysis used the Aikens Index and inter-rater reliability to see the suitability of the content of the indicator with the theory used and to see the agreement of experts in assessing the developed social care indicators. The results of the research based on the needs analysis by surveying 25 students from student organization members in three universities through quota, purposive sampling, and interviews found that 80% of students were involved in BEM social activities, and 72% of students agreed to integrate social activities of student organizations in PAI learning. The results of the Aiken Index content validity test of six skill indicators and four social care attitude indicators were a minimum score of 0.83 and a highest score of 0.91. The reliability test result is 0.64. These results indicate that three experts have agreed upon the content of social care indicators, and then it is feasible to construct a validity test to find out the indicators developed that can measure students' social attitudes and skills using the theory used.